Energy dissipation during impacts of spheres on plates: Investigation of developing elastic flexural waves. (February 2017) - Boettcher, Ronny; Russell, Alexander; Mueller, Peter
Highlights: Derivation of a model for improved energetic analysis by modifying Zener's model. Modeling the impact process as three distinct phases. Comprehensive analytical alternative to the model of Koller. Experimental validation of the proposed model using free fall tests. Abstract: The model of Zener describing the energy dissipation during an impact process due to a simple flexural wave has been modified by dividing the impact process into three phases. For this purpose, crucial results from the model of Koller have been used which describes the same energy dissipation exclusively with longitudinal and transversal waves. The resulting modified model represents a comprehensive analytical alternative to the model of Koller showing a direct relation to the model of Hunter. The modified model approximates the experimental values well and describes them better than the original model of Zener or the model of Koller. For the comprehensive investigation of the influence of the (developing) flexural wave, elastic as well as elastic–plastic materials have been used as model materials for the experiments. Graphical abstract: